All‐Solution‐Processed Indium‐Free Transparent Composite Electrodes based on Ag Nanowire and Metal Oxide for Thin‐Film Solar Cells. (7th January 2014) - Kim, Areum; Won, Yulim; Woo, Kyoohee; Jeong, Sunho; Moon, Jooho
<x xml:space="preserve">Abstract</x> Fully solution‐processed Al‐doped ZnO/silver nanowire (AgNW)/Al‐doped ZnO/ZnO multi‐stacked composite electrodes are introduced as a transparent, conductive window layer for thin‐film solar cells. Unlike conventional sol–gel synthetic pathways, a newly developed combustion reaction‐based sol–gel chemical approach allows dense and uniform composite electrodes at temperatures as low as 200 °C. The resulting composite layer exhibits high transmittance (93.4% at 550 nm) and low sheet resistance (11.3 Ω sq‐1), which are far superior to those of other solution‐processed transparent electrodes and are comparable to their sputtered counterparts. Conductive atomic force microscopy reveals that the multi‐stacked metal‐oxide layers embedded with the AgNWs enhance the photocarrier collection efficiency by broadening the lateral conduction range. This as‐developed composite electrode is successfully applied in Cu(In1‐x, Gax)S2 (CIGS) thin‐film solar cells and exhibits a power conversion efficiency of 11.03%. The fully solution‐processed indium‐free composite films demonstrate not only good performance as transparent electrodes but also the potential for applications in various optoelectronic and photovoltaic devices as a cost‐effective and sustainable alternative electrode.